Lenin : a new biography - Volkogonov, D. A. (Dmitrii Antonovich); Shukman, Harold, 1931- (New York : Free Press, 1994)
For years, westerners have wondered what secrets were preserved not only in the KGB archives, but also in dozens of other off-limits locations. Now that Dmitri Volkogonov, historian and former general in the Soviet Army, has been entrusted with the management of the archives as a Special Assistant to Boris Yeltsin, we at last have a chance to find out. For the last three years he has combed through more than 3700 once-secret documents covering every piece of information in the archive system concerning Vladimir Ilyitch Lenin and his legacy. He has woven this mountain of information into a compelling story of the Soviet founding father and the system he created.
Volkogonov offers a radical departure from the traditional interpretation of Lenin as an idealist. Many of the characteristics of so-called Stalinism, he shows, arose in Lenin's lifetime, often on Lenin's direct orders. From the creation of concentration camps, to brutal repression of the church and the media, to the strategic cultivation of a cult of personality, Lenin's leadership was cruel and totalitarian. Volkogonov also offers select revelations from the post-Lenin years in order to demonstrate that the worst excesses of the Soviet state all had their roots in its founding father. In Volkogonov's words, for years "we asked ourselves where Stalin had acquired the cruelty which he inflicted on his fellow countrymen. None of us - the present author included - could begin to imagine that the father of domestic Russian terrorism, merciless and totalitarian, could have been Lenin."
Includes bibliographical references (p. [485]-509) and index.
Abridged translation of: Lenin : politicheskii portret.
Keywords: Lenin, Vladimir Ilich, -- 1870-1924.; Heads of state -- Soviet Union -- Biography; Soviet Union -- History -- 1917-1936.